Determinan Penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) di Wilayah Kerja Puskesmas - Mili Arthanedi Jumetan; Pius Weraman; Marylin Junias (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the factors that influence the use of the Long-Term Contraceptive Method (MKJP) in the working area of the Batakte Health Center, Kupang Regency in 2021. The method used is descriptive analytic with a cross-sectional design. The data obtained were analyzed using the chi-square test. The results showed that the husband's knowledge and support factor obtained a p-value of 0.000, while the individual's value/trust was 0.038. In conclusion, there is a significant relationship between knowledge, husband's support and individual values/beliefs with the use of MKJP in the Batakte Health Center Work Area, Kupang Regency in 2021. Keywords: Husband's Support, Long Term Contraception Method, Individual Values/Beliefs, Knowledge